PLANTING TIME AND N NUTRITION ON CELL MEMBRANE THERMOSTABILITY, BOLLS’ RETENTION AND FIBRE TRAITS IN COTTON - M. F. Saleema; M. F. Bilala; S. A. Anjuma; H. Z. Khana; M. Sarwara; W. Farhadb (Journal of Animal and Plant Sciences, 2014)
Bolls retention in cotton was assessed under varying temperature regimes and nitrogen rates in field conditions for two consecutive years, 2009 and 2010. Treatments comprised March and May planting (main plots) of a Bt and a non-Bt variety (sub plots) at three nitrogen levels (115, 145 and 175 kg ha-1) kept in sub-sub plots. Means showed more opened bolls and less insects’ damaged, un-opened and total bolls on a plant in mid March planting than in mid May planting during both years. Varietal comparison showed more opened bolls; un-opened bolls and less number of insects’ damaged bolls per plant in FH-113. Among nitrogen levels more insects’ damaged bolls, opened as well as un-opened bolls and total bolls per plant were recorded with 175 kg N ha-1 and minimum with 115 kg N ha-1. Maximum number of insects’ damaged bolls per plant was recorded in CIM-496 at mid may planting while minimum in FH-113 at mid March planting. FH-113 showed more cell membrane thermo stability (heat tolerance) both in early and late planting than CIM-496. Quality characters were most affected by varieties, least by nitrogen and not by sowing date.
Keywords: Heat tolerance; Bolls retention; Fiber quality; Bt and non-Bt; nitrogen and sowing dates